The Pragmatic Theory of Politeness in TV Subtitling - Pavlović, Nataša (Array, 2003)
Subtitling for television is an area that has only recently come into focus of translation studies. This paper, based on our recent research in the area, highlights the specific features of subtitling and then illustrates how these may serve to shed light on particular aspects of the translation process. The pragmatic notion of politeness is examined against the backdrop of the many constraints inherent to the subtitling technique.